(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
The article examines modern pedagogical technologies applied in environmental education and upbringing for preschool and school-aged children. Special attention is given to information and communication technologies (ICT), project-based and research activities, problem-based learning, game-based methods, case technologies, STEAM approaches, and service learning. Their impact on the development of environmental culture, critical and systemic thinking, practical skills, and social responsibility is analyzed. International and local experiences, including projects in Europe, Scandinavia, the USA, Canada, Asia, and pilot programs in Uzbekistan, are presented. The necessity of integrating innovative methods to enhance the quality of environmental education amid global ecological challenges is substantiated.